Understanding sustainability for socially responsible investing and reporting - Marianne Bradford; Julia B. Earp; Paul F. Williams (Journal of Capital Markets Studies (JCMS), 2017)
Purpose - The purpose of this paper is to determine what types of sustainability activities companies are reporting and whether persons external to the companies understand how those reported activities correspond to the companies' narratives about sustainability. That is to ascertain how people interpret the meaning of the activities included in the sustainability reports. Design/methodology/approach - From a sample of sustainability reports prepared by Global Reporting Initiative (GRI) guidelines, the authors identified the distinct activities reported. The authors prepared a survey comprised of these activities and asked a sample of people knowledgeable about business and investing to evaluate each activity on the extent to which they are relevant to sustainability performance. The responses were then factor analyzed to identify the most important dimensions of sustainability these persons employed to relate the activities to sustainability. Findings - The dimensions employed by the subjects differed in some significant ways from those dimensions used to construct the GRI format. Subjects evaluated sustainability efforts as primarily efforts of being a good citizen with sustainability an end in itself rather than as constraint to be respected in achieving profitability goals. Research limitations/implications - The study is a first attempt so results are preliminary, i.e. suggestive but not definitive. Though preliminary an intriguing implication is that closure on a sustainability reporting structure would be premature. More effort needs to be devoted to provide more clarity on the concept of corporate sustainability and what its implications are for corporate behavior. Practical implications - Given the results that sustainability be regarded as a corporate end, what is the role of the corporation in society seems still to be disputatious. Sustainability may not be something achievable without changes in corporate law. Originality/value - The study is an early attempt to assess the potential alternative narratives about corporate sustainability. Its value lies in providing insights into the age-old question of what should be the role of the corporation in a free society.
Keywords: 330; CSR; Sustainability; Global reporting initiative; Sustainability reporting; Stakeholder narratives